(untitled) (Linguostylistic Studies, 2021)
This scientific article-essay analyzes the elite philological personality of Professor Nadiia Babych, her creative manner, and its influence on the formation and development of her student, his formation as a teacher. The article reveals how Teacher and Student’s common values ​​predict common life goals and aspirations. The author argues that the mastery and pedagogical values ​​are developed in the process of pedagogical activity, when their subjectivation takes place. The level of subjectivation of pedagogical values ​​is an indicator of personal and professional development of a teacher. The key finding states that sensitive personal-memorial receptivity humanizes the memories of life relationships and preserves their warmth.